Análise do perfil vocal de corretores imobiliários na cidade de Curitiba - Gomes, Marcelo Brim (2014)
There has been a concern towards the vocal health of real estate agents and it was found that these professionals use oral expressions that demand a tremendous effort to vocal functionality. Objective: To analyze the vocal profile through the RASATI scale and VHI vocal symptoms identified in real estate agent from Curitiba. Method: 78 real estate agents participated in this research, aging between 20 and 75 years old. It was performs a perceptual- auditory evaluation with RASATI scale and an analysis of voice handicap through a Voice Handicap Index (VHI) questionnaire. It was used for the auditory perceptual judgment of voice the following: prolonged vowel sound of /a/, counting numbers from 0 to 20 and spontaneous speech. Results: The results showed that there is a considerable percentage of professionals with voice handicap index that are considered moderate (5.13%) or severe (2.56 %) with predominant scores on the functional domains (M = 4.86) and organic (M = 4.65). In this condition, the professional presents sensations and laryngeal symptoms of discomfort such as pain, burning, fatigue and vocal fatigue. The findings of auditory perceptual from the RASATI scale are Hoarseness (Light =32 %, Moderate = 6.4%; Intense = 1.3%), Roughness (Light = 23.1 %, Moderate = 2.6 %) Breathiness (Light = 5.1%; Moderate = 2.6%) and tension (L = 9.0 %). Conclusion: The low VHI emotional domain reveals the lack of awareness from the real estate agent regarding the importance and care of their voices in the workplace, since the organic and functional domains are easier to be detected by the patient because they are physical and objective sensations, while the emotional score is more related to sensations that are not presented at the moment of this work.